The rise of urban locations in screendance - Llerena Fernández, Alma (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This work arises as a result of a research whose objectives are to identify the types of scenic spaces, floors and locations used by screndances. For this purpose, we have analyzed 152 works chosen from the official selections of specific Spanish festivals, since their creation until 2018. For the analysis we have created an ad hoc model of nine variables and 44 categories. From the analysis we can conclude that screendance works preferentially uses framing centered on open and usually flat spaces, which are located in urban environments, generally indoors, with specific floors that bring meaning to the choreography or narrative of the videodance.